Аналитический обзор биомедицинских средств дистанционного мониторинга пациентов с артериальной гипертезией - Сокол, Евгений Иванович; Колесник, Константин Васильевич; Коваль, С. Н.; Снегурская, И. А.; Юшко, К. А. (Издательство "Точка", 2017)
In modern conditions, the problem of effective treatment of hypertension is of particular relevance. In this regard, there is a need to monitor the patient's condition not only in a hospital under the direct supervision of the attending physician, but also in the period between such stationary observations. An important role in the treatment of a patient can be provided by biomedical means of remote monitoring of patients with arterial hypertension, allowing controlling the basic parameters of the patient's body remote from the hospital. When creating such complexes, it is necessary to use the scientific and technical potential of modern medical devices. Their analytical review was carried out.
Keywords: дистанционный мониторинг; мониторинг состояния пациента; биомедицинские средства мониторинга; система телемедицинского мониторинга